Human Reconnection to Nature: An Ecopsychological Appeal in Corona Time Poetry - Baral, Prabitra Raj (The Outlook: Journal of English Studies, 2020)
Ecopsycology emphasizes on the intrinsic bond between humans and nature for mutual well-being. This article examines how poetry of corona time expresses human anxieties of environmental loss and sense of alienation from nature and how it makes people aware of their inherent sense of emotional attachment with natural system for their happiness, well-being and meaningful life. The objective of this paper is to investigate humans’ alienation from nature and their efforts for reconnecting to it. To achieve this, the paper evaluates the selected poems using theoretical modality of ecopsychology propounded by Theodore Roszak and Robert Greenway. As a piece of qualitative research, it incorporates interpretive and analytical approaches following the techniques of close reading of the selected texts. Along with the relevant observations of critics, the focus lies on the thematic and textual analysis of the selected poems. The findings of the research unveil that corona time poetry depicts humans’ alienation from nature as a consequence of their indifference to and domination upon it, and the only way for their well-being is reconnection to it.